2018
DOI: 10.1007/s00259-018-4062-8
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT imaging in detecting and guiding management of invasive fungal infections: a retrospective comparison to conventional CT imaging

Abstract: FDG PET/CT was able to localize clinically occult infection and dissemination and was particularly helpful in demonstrating response to antifungal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 32 publications
0
69
1
Order By: Relevance
“…Small studies have also demonstrated high clinical impact of FDG‐PET/CT in patients with neutropenic fever (NF) of unclear cause, with benefits of de‐escalating or rationalising antimicrobials, of directing further investigation such as bronchoscopy or tissue sampling and establishing an aetiological diagnosis of NF . There is emerging evidence that FDG‐PET/CT is more sensitive for invasive fungal infection (IFI), its dissemination and response to therapy compared to traditional computed tomography (CT) . Despite this, Medicare rebate for FDG‐PET/CT scanning is still restricted to staging and restaging of some specific malignancies, with no rebate for any infection indication, significantly limiting access for Australian patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small studies have also demonstrated high clinical impact of FDG‐PET/CT in patients with neutropenic fever (NF) of unclear cause, with benefits of de‐escalating or rationalising antimicrobials, of directing further investigation such as bronchoscopy or tissue sampling and establishing an aetiological diagnosis of NF . There is emerging evidence that FDG‐PET/CT is more sensitive for invasive fungal infection (IFI), its dissemination and response to therapy compared to traditional computed tomography (CT) . Despite this, Medicare rebate for FDG‐PET/CT scanning is still restricted to staging and restaging of some specific malignancies, with no rebate for any infection indication, significantly limiting access for Australian patients.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 There is emerging evidence that FDG-PET/CT is more sensitive for invasive fungal infection (IFI), its dissemination and response to therapy compared to traditional computed tomography (CT). 7,8 Despite this, Medicare rebate for FDG-PET/CT scanning is still restricted to staging and restaging of some specific malignancies, with no rebate for any infection indication, significantly limiting access for Australian patients. As a consequence, PET scanner access is limited or nonexistent in certain regions and health services in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical setting, [ 18 F]FDG PET/CT has been used to visualize IC and Candida lung abscesses ( Bleeker-Rovers et al, 2005 ; Avet et al, 2009 ), but its accuracy in identifying IC or invasive fungal infections in general remains to be fully proven, since the radiopharmaceutical is unable to discriminate between infectious and non-infectious pathologies or to differentiate between bacterial and fungal infections and inflammation ( Rolle et al, 2016 ). Nevertheless, a recent retrospective comparison of [ 18 F]FDG PET/CT to conventional CT imaging has shown the utility of [ 18 F]FDG PET/CT as a non-invasive procedure for monitoring responsiveness of Candida and mold infections to antifungal drugs once the identity of the infecting organisms has been established using conventional diagnostic procedures ( Douglas et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…FDG was first synthesized by Ido et al in 1978 [100] and it is an analogue of glucose whereby the C2 hydroxyl group is replaced by the radioactive fluorine atom 18 F. The accumulation of FDG reflects the metabolic requirements of cells, and as such, it has been used to detect cancer cells, which present metabolic demands that are different from most normal cells [101]. Recently FDG has been also used in PET/CT imaging for detecting and guiding management of invasive fungal infections, with improved performance over CT alone for the localisation of infection, dissemination and response to therapy in human patients [102].…”
Section: Alternative Modalities For Non-optical In Vivo Imagingmentioning
confidence: 99%